Including Children with Visual Impairment in General Class: Teacher’s Lived Experience (Siddhajyoti Interdisciplinary Journal, 2023)
This study aimed to explore the perception of general teacher with the major challenges while teaching students with visual impairment in general class. The qualitative research design with hermeneutics phenomenology was employed in the study. It also delineates how general teacher of integrated school use potential resource to assimilate children with visual impairment in mainstream setting. Four teachers from two integrated schools located in Kathmandu valley having different disciplines were purposively selected. The profound interview had been conducted in face to face situation through open ended questions in their existing position. The interview responses were transcribed as verbatim and triangulated among participants. The data were analyzed by using narrative analysis and thematic technique to develop theme under the insight of literature review. From the teacher’s narratives, unusual behavior, problem of intention, uncertainty of job placement and unwillingness of reading were deduced as major challenges to include children with visual impairment in general class. The essence of study contributes to over[1]view the challenges and adopts appropriate strategies to create inclusive environment in regular classroom. This also energize teacher to professional development from the lens of diversity management approach. The essence of study can contribute to set up inclusive atmosphere in regular class room and to energize professional development from the lens of inclusive approach.